Women and Credit Market in Malaga. A Study Through the Notarial Deeds at the End of the 18th Century - García Gil, Elizabeth (Revista de Historia Social y de las Mentalidades, 2023)
The aim of this work is to know the participation of women in Malaga credit market at the end of the Old Regime, especially in their role as creditor. The mortgage loan was one of the credit instruments that was registered in a notary, in order to formalize and guarantee the financed benefit. On the one hand, obligations contained in the notarial protocols of Malaga int the late 18th century have been analyzed. On the other hand, in order to get closer to the personal and professional trajectory of these women lenders, other documentary sources such as wills, population censuses and mortgages have been examined.